Analisis Prinsip Sharia Compliance Terhadap Implementasi Akad Murabahah Di Perbankan Syariah Indonesia - Fahmi Makraja; Muhammad Nuur Iman bin Suip (Sociale : Journal of Social Science, 2026)
This study aims to critically analyze the implementation of Murabahah contracts in Indonesian Islamic Banking from the perspective of Shari'ah Compliance principles. Although Murabahah is fundamentally defined as a sale and purchase transaction (bai') with an agreed profit margin, its practical implementation often shows distortions that distance it from the pure essence of sale and purchase and make it more similar to a debt financing scheme. The main distortion is identified in the minimal role of the bank as the seller who owns and controls the object of the goods (qabdh), as well as the use of wakalah contracts, which often obscure the transfer of risk and actual ownership. The method used is descriptive qualitative analysis with a contemporary fiqh muamalah approach and Sharia banking regulations applicable in Indonesia (DSN-MUI Fatwa and PBI/POJK). The results of the analysis show that although formally and legally the Bank has fulfilled the document requirements, substantively several practices, such as determining the selling price based on conventional interest calculations (even though it is termed margin) and the absence of full ownership risk, weaken the clear separation between Sharia and conventional principles